2022
DOI: 10.1093/nar/gkac854
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAlncMREFpromotes myogenic differentiation and muscle regeneration by interacting with the Smarca5/p300 complex

Abstract: Long noncoding RNAs (lncRNAs) play important roles in the spatial and temporal regulation of muscle development and regeneration. Nevertheless, the determination of their biological functions and mechanisms underlying muscle regeneration remains challenging. Here, we identified a lncRNA named lncMREF (lncRNA muscle regeneration enhancement factor) as a conserved positive regulator of muscle regeneration among mice, pigs and humans. Functional studies demonstrated that lncMREF, which is mainly expressed in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…A few studies have undertaken global analyses of lncRNAs in regeneration, for instance following injury in skeletal muscle (Gonçalves et al 2017) or during cardiac regeneration in zebrafish (Lumley et al 2021). Specific lncRNAs have also been linked to regeneration: H19 is associated with nerve degeneration and regeneration in rats (Li et al 2022), and mucosal regeneration in mice (Geng et al 2018); lncMREF is a positive regulator of muscle regeneration in mice, pigs and humans (Lv et al 2022); CR46040 has recently been identified as crucial for the proliferation of intestinal stem cells in response to injury in Drosophila (Xu et al 2023). In the context of wing regeneration, we have identified a subset of 131 DE lncRNAs that could participate in the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have undertaken global analyses of lncRNAs in regeneration, for instance following injury in skeletal muscle (Gonçalves et al 2017) or during cardiac regeneration in zebrafish (Lumley et al 2021). Specific lncRNAs have also been linked to regeneration: H19 is associated with nerve degeneration and regeneration in rats (Li et al 2022), and mucosal regeneration in mice (Geng et al 2018); lncMREF is a positive regulator of muscle regeneration in mice, pigs and humans (Lv et al 2022); CR46040 has recently been identified as crucial for the proliferation of intestinal stem cells in response to injury in Drosophila (Xu et al 2023). In the context of wing regeneration, we have identified a subset of 131 DE lncRNAs that could participate in the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…As studied, lentiviral infection is performed to deliver target transgenes to 293T cells with the robust expression of stable cell lines [21]. In this study, we developed the lentivirus in 293T cells using three vectors: 2.1 µg pLV3-CMV-MCS-3×FLAG-CopGFP-Puro or pLV3-CMV-SATB2 (pig)-3×FLAG-CopGFP-Puro, 1.4 µg psPAX2 (MiaoLingBio, Wuhan, China), and 0.7 µg PDM2.G (Addgene, Watertown, MA, USA).…”
Section: Lentivirus Packagingmentioning
confidence: 99%
“…The 3′-UTRs contain important elements, such as hexameric PAS and cytoplasmic polyadenylation elements (CPE), which regulate cytoplasmic polyadenylation and interact with post-transcriptional factors to influence mRNA degradation and translation [ 21 , 22 ]. APA regulates gene expression and function in a cell- and tissue-specific manner [ 10 , 23 ], and it has been demonstrated that long non-coding RNAs (lncRNAs) exert impacts pig traits [ 24 ], especially those related to pig reproductive traits [ 25 ].…”
Section: Introductionmentioning
confidence: 99%